Implementation of Autolytic Debridement Using Zinc Cream to Reduce Necrotic Tissue in Patients with Chronic Wounds in the Gunung Meriah Community Health Center Working Area - Dasrina; Kamalia Pohan; Eka Sutrisna; Risardi Ramandha (Poltekkes Kemenkes Aceh, 2026)
Chronic wounds are wounds that are difficult to heal and have a prolonged healing phase. A characteristic feature is the presence of necrotic tissue (dead tissue), which may be yellow or black. One technique used to remove dead tissue is autolytic debridement. Autolytic debridement is a crucial element of wound bed preparation, defined as the removal of foreign bodies or damaged, injured, and infected tissue from the wound until the surrounding healthy tissue is exposed. Supporting this process requires a dressing—specifically zinc cream—which facilitates autolytic debridement (sloughing off necrotic tissue), prevents trauma during dressing changes, reduces unpleasant odors, and maintains a moist environment conducive to granulation. This case study employed a nursing process approach involving a single subject in Lae Butar Village over the period of March 20–29, 2026. The results demonstrated that the use of autolytic debridement and zinc cream dressings effectively reduced black and yellow necrotic tissue in the chronic wound patient; specifically, the tissue composition shifted from 20% eschar (black) and 70% slough (yellow) at the first implementation to 5% eschar and 20% slough by the fourth implementation. This study aimed to evaluate the application of autolytic debridement with zinc cream in reducing necrotic tissue in a chronic wound patient. The findings offer a recommendation for nurses to utilize autolytic debridement combined with zinc cream dressings as a method for reducing necrotic tissue levels in patients with chronic wounds.